2022
DOI: 10.3390/nano12050835
|View full text |Cite
|
Sign up to set email alerts
|

Strain Engineering: A Pathway for Tunable Functionalities of Perovskite Metal Oxide Films

Abstract: Perovskite offers a framework that boasts various functionalities and physical properties of interest such as ferroelectricity, magnetic orderings, multiferroicity, superconductivity, semiconductor, and optoelectronic properties owing to their rich compositional diversity. These properties are also uniquely tied to their crystal distortion which is directly affected by lattice strain. Therefore, many important properties of perovskite can be further tuned through strain engineering which can be accomplished by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 131 publications
0
13
0
Order By: Relevance
“…Additionally, strain-engineering through the use of alternative substrates and nanocomposite epitaxial relationships may allow for further tuning of structural and optical properties. [44,[66][67][68] We would also like to emphasize that there exists the possibility of an optical cascade for downgraded emission. As discussed previously, [17][18][19] energy transfer for Ce 3+ → Tb 3+ → Eu 3+ can occur.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Additionally, strain-engineering through the use of alternative substrates and nanocomposite epitaxial relationships may allow for further tuning of structural and optical properties. [44,[66][67][68] We would also like to emphasize that there exists the possibility of an optical cascade for downgraded emission. As discussed previously, [17][18][19] energy transfer for Ce 3+ → Tb 3+ → Eu 3+ can occur.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, strain‐engineering through the use of alternative substrates and nanocomposite epitaxial relationships may allow for further tuning of structural and optical properties. [ 44 , 66 , 67 , 68 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, closed and quasi-closed shell electronic configurations of cation species ( d 10 , d 6 , d 3 ) are the best candidates to reduce localization of holes in oxygen ions and minimize colorization from the metal d–d excitation. In this line, some new p -type TCOs based on Cr 3+ oxides ( d 3 in octahedral configuration) have been already identified among which Sr-doped LaCrO 3 appears as a strong candidate with reasonably high transparency and p -type conductivity. Importantly, the ability to grow these materials as epitaxial films can be used as a lever to tune the physical properties. In fact, it has been recently demonstrated that electric conductivity of Sr-doped LaCrO 3 films grown by molecular beam epitaxy (MBE) can be finely tuned through epitaxial strain . Nevertheless, when evaluating the suitability of an oxide material to be used as a TCO, along with high electrical conductivity and optical transmittance, it is important to consider cost-effective and sustainable processing techniques.…”
Section: Introductionmentioning
confidence: 99%
“…A great many phenomena in materials science and solid-state physics and chemistry are mediated by strain, including phase transitions in conventional and quantum materials, plasticity and myriad material failure modes, and surface reconstruction and chemistry. Large static strains of several percent can be applied to bulk or thin samples up to the onset of plasticity or fracture [10][11][12][13][14]. However, since kinetic effects can lead to distinct differences from quasi-static behavior, approaches capable of generating fast actuation mechanisms to explore material responses to dynamic strain are of keen interest.…”
mentioning
confidence: 99%